Design recommendations for energy systems: a UK energy community study - Panagiotou, Konstantina; Klumpner, Christian; Sumner, M.; Wheeler, Patrick (2017)
One of the key elements towards a decentralised energy sector is the consumers’ choice and participation, as the concept of energy prosumer is gaining more and more ground and energy community projects are spouting across UK. In order for the upcoming energy systems to deliver their potential financial benefits, holistic design needs to be assessed by quantifying the most relevant design aspects (size and operation) and the energy flow through the energy system. Thus, the predominant aim of this study is to provide design recommendations for energy systems suitable to be used in an energy community, which can be expanded to futuristic energy systems. The aspects which were considered include: detailed consumption and generation profiles, charging patterns and limitations that a real energy storage systems of given rated energy and power will impose to energy systems.